X-ray Crystal Structures and the Facile Oxidative (Au−C) Cleavage of the Dimethylaurate(I) and Tetramethylaurate(III) Homologues - Zhu, Dunming; Lindeman, Sergey V; Kochi, Jay K (Organometallics, 1999)
Dimethylaurate(I) has been prepared as the crystalline tetrabutylammonium salt for comparison with the known tetramethylaurate(III) analogue. The linear structure of dimethylaurate(I) and the square-planar structure of tetramethylaurate(III) have both been confirmed by X-ray crystallography. One-electron oxidation of dimethylaurate(I) by either ferrocenium or arenediazonium cations produces the metastable dimethylgold(II) intermediate, which can be trapped as the paramagnetic 9,10-phenanthrenequinone (PQ) adduct. Otherwise, dimethylgold(II) is subject to rapid reductive elimination of ethane and affords metallic gold (mirror). The analogous oxidation of tetramethylaurate(III) by ferrocenium, arenediazonium, or nitrosonium cations also proceeds via electron transfer to generate the putative tetramethylgold(IV) intermediate. The highly unstable (CH3)4AuIV spontaneously undergoes homolytic cleavage to produce methyl radical and the coordinately unsaturated trimethylgold(III), which can be intercepted by added triphenylphosphine to afford Me3AuIIIPPh3.